Analysis of the Review of the Standard Inpatient Class Policy (KRIS) as a Replacement for the BPJS Health Class System in Improving Health Service Equity Based on Presidential Regulation Number 59 of 2024 - Hakiki, Bela Amru (Asosiasi Penelitian dan Pengajar Ilmu Sosial Indonesia, 2025)
Changes in the health insurance system in Indonesia continue to evolve, one of which is implementing the Standard Inpatient Class (KRIS) policy as a replacement for the BPJS Health class system based on Presidential Regulation (Perpres) Number 59 of 2024. This policy is designed to unify healthcare classes to reduce disparities in healthcare access and quality in Indonesia. However, its implementation is faced with key challenges, including hospital infrastructure readiness, limited human resources, and criticism from various parties, including patients and healthcare providers. This study uses a qualitative approach with descriptive methods to review various policy documents, relevant literature, and legal and social perspectives related to policy implementation. The results show that although KRIS has the potential to reduce disparities in access to health services, its implementation requires more attention to the readiness of health facilities, strengthening management systems, and budget adjustments to support optimal operations. Furthermore, this policy requires the active involvement of the community and health workers in the evaluation and decision-making process so that the policy is more responsive to the real needs in the field. The theoretical approaches used, such as public policy theory and progressive law, highlight the importance of cooperation between the government, healthcare providers, and communities to ensure effective and equitable implementation of KRIS. This research suggests improving hospital infrastructure, continuous training for health workers, and strengthening a transparent monitoring system to ensure the success of this policy. This research is expected to make a positive contribution to the formulation of health policies that are more inclusive and sustainable and can serve as a reference in efforts to realize a more equitable and fair health service system for all Indonesians.